Packed Red Cell (PRC) Blood Needs on Thalasemia Patients at Hospital. Moewardi in October-December 2021 - Amellia Kemastha; Syarifah; Kunti Dewi Saraswati (International Journal of Seocology, 2023)
Patients with thalassemia disease in Indonesia are classified as high, this is indicated by the fulfillment of the need for blood transfusions that are carried out regularly so as to create a balance between supply and demand. To describe the fulfillment of PRC needs in thalassemia patients at the hospital. Moewardi in October-December 2021. Descriptive research with a quantitative approach and cross-sectional research design. The research population was 222 requests by random sampling. Data collection using secondary data processed using SPSS and Microsoft Excel. Univariate data analysis in the form of tables, diagrams and descriptions. Amount of fulfillment in October-December 2021 was 222 patients. By gender 118 (53.2%) patients and male 104 (46.8%) patients. Fulfillment of needs with blood type A positive 61 (27.5%), B positive 54 (24.3%), O positive 88 (39.6%), AB positive 19 (8.6%). Based on age with a range of 1-10 years 119 (53.6%), 11-20 years 71 (32.0%), 21-34 years 28 (12.6%), 35 years 4 (1.8%). Most of the needs were met by female sex as many as 118 patients with positive rhesus blood type and dominated by the age of 1-10 years.